Fluktuationen in der Geschichte: Ein kurzer Abschied von den langen Wellen - Müller Karl H. (Österreichische Zeitschrift für Geschichtswissenschaften, 2007)
The article reconstructs the important influence of cycle theories on the explanation of processes in business and society after Kondratieff and Schumpeter. So-called long waves are discussed on the basis of five major innovations with network character in the realm of infrastructure (railways, electrification, roads, airports, Internet). Here the author claims that various networks do not just inform each other but also that it is necessary to take a look at the connections of large, medium-sized and small innovations. For this task the perspective of long waves is not sufficient and it is thus unsuitable. Instead the article backs an alternative perspective, namely one that is based on fluctuation and networks.